Wavelength of Experimental LEDS: Hardness, Elastic Modulus, Degree of Conversion and Temperature Rise of a Microhybrid Composite - Ana Paula Bonilauri Ferreira; Paulo César Soares Júnior; Evelise Machado Souza; Rodrigo Nunes Rached; Sérgio Henrique Pezzin; Sérgio Vieira (Materials Research, 2015)
The aim of this study was to evaluate the effect of different peak wavelengths (450nm, 468nm and 490nm) of experimental LEDs on hardness, elastic modulus, degree of conversion and temperature rise of a microhybrid resin composite – Venus® (Heraeus Kulzer). Hardness and elastic modulus were determined by nanoindentation technique (n=5), degree of conversion was measured by FTIR (n=5) and temperature rise was measured with a thermistor (n=30). Data were submitted to ANOVA and multiple comparisons tests (α=0.05). Mechanical properties and degree of conversion (p<0.001) were superior on the top surfaces of the specimens. 468nm showed the highest mechanical properties values. There was no statistical difference in the degree of conversion (p=0.51) and in temperature rise (p=0.06) among all LEDs. Hardness and elastic modulus were influenced by LED´s wavelength, whereas degree of conversion and temperature rise were not influenced.